Early unpredictability predicts increased adolescent externalizing behaviors and substance use: A life history perspective. (9th December 2015) - Doom, Jenalee R.; Vanzomeren-Dohm, Adrienne A.; Simpson, Jeffry A.
Abstract: According to evolutionary life history models, environmental harshness and unpredictability can both promote a fast life history strategy characterized by increased risk taking and enacting short-term, opportunistic behaviors. The current longitudinal study tests whether environmental unpredictability during childhood has stronger effects on risky behavior during adolescence than harshness, and whether there may be an early "sensitive period" during which unpredictability has particularly strong and unique effects on these outcomes. Using data from the Minnesota Longitudinal Study of Risk and Adaptation, prospective assessments of environmental unpredictability (changes in residence, cohabitation, and parental occupation) and harshness (mean socioeconomic status) from birth into adolescence were used to predict self-reported externalizing behaviors and substance use at age 16 ( N = 220). Exposure to greater early unpredictability (between ages 0 and 5) predicted more externalizing behaviors as well as more alcohol and marijuana use at age 16, controlling for harshness and later unpredictability (between ages 6 and 16). Harshness predicted adolescent substance use, and later unpredictability predicted adolescent externalizing behaviors at the trend level. Early unpredictability and harshness also interacted, such that the highest levels of risk taking occurred in individuals who experienced more early unpredictability and lived in harsher environments. Age 16 externalizing behaviors, but not substance use, mediated the association between early unpredictability and externalizing/criminal behaviors at age 23. We discuss how exposure to early environmental unpredictability may alter biological and social–cognitive functioning from a life history perspective.